Exploring Psychological Well-being and Integrated Care Approaches in Older Adults: A Quantitative and Descriptive Analysis of Key Factors in Lifelong Education - Rosser Limiñana, Pablo; Soler, Seila (International Journal of Physical Medicine & Rehabilitation, 2024)
Background: This pilot study addresses the importance of psychological and emotional well-being in older adults, focusing on the population of the Lifelong Learning University for older adults in Alicante (Spain). It investigates how various psychosocial and educational factors impact their quality of life and personal satisfaction. The aim is to identify key elements influencing the well-being of this population, with special attention to self-esteem, self-efficacy, satisfaction with personal achievements, and the integration of patient care approaches. It seeks to positively influence them through education, considering lifelong education as an integral part of a holistic care model that promotes active and healthy aging. Methods and findings: A descriptive and quantitative analysis was conducted with a small sample size of 15 older adults, serving as a pilot test to be implemented in a second phase with over a hundred participants. A questionnaire based on Ryff’s psychological well-being scale was utilized. The results indicated significant variations in well-being perception related to age and other demographic factors. A high degree of personal pride and confidence in opinions was observed, although challenges in expressing opinions and susceptibility to external convictions were also noted. Cronbach’s Alpha showed moderate to low reliability, influenced by the substantial age variability causing dispersion in opinions, which is considered acceptable in studies of this nature. Conclusion: The study underscores the significance of addressing specific aspects of psychological well-being in older adults, including self-esteem, communication skills, and the necessity for integrated care approaches. The findings highlight the importance of personalized interventions and educational strategies, which are complemented by integrative patient care techniques, to enhance the quality of life for this demographic. This integrated approach suggests a broader framework for supporting older adults, not only through targeted educational programs but also by incorporating holistic care elements that address their comprehensive health and well-being needs
Keywords: psychological well-being; older adults; self-esteem; communication; lifelong education